Aging, economic growth, and old-age security in Asia - Park, Donghyun; Lee, Sang-Hyop; Mason, Andrew 1947- (Edward Elgar, 2012)
Population aging is perhaps the single biggest econmoic and social obstacle confronting Asia's future. The region-wide demographic transition towards an older population is fundamentally reshaping the demographic landscape, and is giving rise to two key socio-economic challenges. This timely book provides an in-depth analysis of these challenges and presents concrete policy options for tackling them.